Immunological dysfunction of children with severe parapneumonic effusion - Rózsai, Barnabás; Simon, Diána; Berki, Tímea; Kiss, Gabriella; Mosdósi, Bernadett (Frontiers in Pediatrics, 2025)
PurposeDespite the worldwide decrease in the incidence of serious pneumococcal infections following the introduction of the 13-valent pneumococcal conjugate vaccines (PCV13), invasive infections still occur. This study aimed to investigate the immunological function of children with severe parapneumonic effusion (PPE) both during their hospitalization and after full recovery.MethodsThis was a prospective, single-center study. Children with PPE were admitted to our clinic between 1 January 2011 and 30 June 2023, and participated in the study. Due to the severity of the effusion, all PPE cases required thoracic drainage and some children also underwent fibrinolysis and/or video-assisted thoracoscopic surgery. Demographic and clinical data and laboratory results were collected at admission. Extended immunological testing was performed at the time of clinical admission and again 6–8 weeks after discharge.ResultsA total of 66 episodes of PPE were identified. During hospitalization, one patient was diagnosed with human immunodeficiency virus infection and another with immunoglobulin A deficiency. Extended immunological evaluation was performed during follow-up in 49 patients. Within this cohort, seven patients were diagnosed with mannose-binding lectin deficiency and three with specific antibody deficiency. In total, immune dysfunction was confirmed in 12 patients. When comparing the immunocompromised and non-immunocompromised groups, the duration of hospitalization was longer in the immunocompromised group, with no other differences observed.ConclusionAlthough the incidence of severe PPE has declined since the introduction of PCV13, immunological evaluation remains essential for identifying underlying immunodeficiencies. Despite vaccination, screening patients with PPE for immune dysfunction is crucial. Early diagnosis and timely treatment can help prevent organ damage and reduce long-term morbidity.